2013
DOI: 10.1115/1.4007795
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Theory for Radial Crack Propagation: Application to Spherical Indentation

Abstract: A simple analytical theory is proposed for estimating the number of radial cracks which will propagate in brittle materials subjected to axisymmetric transverse smface loads. Eirst, an expression is obtained for the stress intensity factor of a traction-free starshaped crack in an infinite elastic membrane subjected to axisymmetric transverse loads. Combining this relation with the critical stress intensity factor criterion for fracture, an implicit expression is obtained which defines the number of cracks as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In addition, the comparison between the numerical simulation and the experimental results showed that the ice plate used in the numerical simulation was symmetrical and uniform, so the cracks were mostly regular, which was difficult to achieve in the experiment. Therefore, due to the difference between the randomness of the cracks and the inhomogeneous mechanical properties of the ice body, it was more important to focus on the damage pattern of the cracks rather than the specific crack properties in the study, which was previously discussed by Li and Chen; Rabczuk; Seagraves and Radovitzky; and Yuan [40][41][42][43]. This also confirmed the complex mechanical properties of the ice under impact loads.…”
Section: Validation Of Compressed Gas Bubble-ice Coupling Modelsupporting
confidence: 67%
“…In addition, the comparison between the numerical simulation and the experimental results showed that the ice plate used in the numerical simulation was symmetrical and uniform, so the cracks were mostly regular, which was difficult to achieve in the experiment. Therefore, due to the difference between the randomness of the cracks and the inhomogeneous mechanical properties of the ice body, it was more important to focus on the damage pattern of the cracks rather than the specific crack properties in the study, which was previously discussed by Li and Chen; Rabczuk; Seagraves and Radovitzky; and Yuan [40][41][42][43]. This also confirmed the complex mechanical properties of the ice under impact loads.…”
Section: Validation Of Compressed Gas Bubble-ice Coupling Modelsupporting
confidence: 67%
“…It is for this reason that the closed-form determination of the stress field near a sharp inclusion or void is crucial for the design of ultra-resistant composites. triangular and Vickers pyramidal indenters [7,9,10] and can emerge during drying of colloidal suspensions in capillary tubes [14,18]. Multiple radial crack patterns are generated after low speed impacts 1 on brittle plates [38].…”
mentioning
confidence: 99%
“…The nanocrack formation is proposed to occur in three steps“bulging,” “initiation,” and “propagation”as revealed by the corresponding images and height profiles (Figure a). The PDMS contains the residual solvent; when thermal evaporation begins ( t Au = 10 nm), the solvent agglomerates and erupts, generating an externally directed force under the Au film so that bulges form in the film . The driving force for the eruption of solvent is assumed to be the evaporation of the internal solvent due to the thermal energy that the deposited atoms transfer to the elastomeric substrate during thermal evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…The PDMS contains the residual solvent; when thermal evaporation begins (t Au = 10 nm), the solvent agglomerates 37 and erupts, generating an externally directed force under the Au film so that bulges form in the film. 38 The driving force for the eruption of solvent is assumed to be the evaporation of the internal solvent due to the thermal energy that the deposited atoms transfer to the elastomeric substrate during thermal evaporation. This eruption imposes a large tensile stress σ erupt ; when the total applied stress σ th + σ erupt exceeds the critical tensile stress σ tensile of Au, cracking occurs during the subsequent evaporation (t Au = 20 nm) (see the estimation of σ erupt and conditions for the film crack initiation of the film in the Supporting Information; Figures S6 and S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%